2011
DOI: 10.1002/qj.1864
|View full text |Cite
|
Sign up to set email alerts
|

Assimilation of water‐vapour airborne lidar observations: impact study on the COPS precipitation forecasts

Abstract: The Convective and Orographically-driven Precipitation Study (COPS) carried out in summer 2007 over northeastern France and southwestern Germany provided a fairly comprehensive description of the low-troposphere water-vapour field, thanks in particular to the deployment of two airborne differential absorption lidar systems. These lidar observations were assimilated using the 3D-Var assimilation system of the Application of Research to Operations at MEsoscale (AROME) numerical weather prediction mesoscale model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…As several studies have already demonstrated a strong and positive impact of the water vapor lidar data on the initial water vapor field of the numerical weather prediction mesoscale model by using the three-or four-dimensional variational method (Wulfmeyer et al, 2006;Grzeschik et al, 2008;Bielli et al, 2012), the MRL-measured data can be assimilated into a nonhydrostatic mesoscale model (NHM) (Saito et al, 2007) by the local ensemble transform Kalman filter (LETKF) method (Kunii, 2014) to improve the initial condition of the water vapor field and consequently the rainfall forecast. Given the temporal and vertical resolutions of the model and the assim-ilation window length, the required measurement resolutions are at most 30 min in time and 200 m in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%
“…As several studies have already demonstrated a strong and positive impact of the water vapor lidar data on the initial water vapor field of the numerical weather prediction mesoscale model by using the three-or four-dimensional variational method (Wulfmeyer et al, 2006;Grzeschik et al, 2008;Bielli et al, 2012), the MRL-measured data can be assimilated into a nonhydrostatic mesoscale model (NHM) (Saito et al, 2007) by the local ensemble transform Kalman filter (LETKF) method (Kunii, 2014) to improve the initial condition of the water vapor field and consequently the rainfall forecast. Given the temporal and vertical resolutions of the model and the assim-ilation window length, the required measurement resolutions are at most 30 min in time and 200 m in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the verification of forecast performance can be more difficult at convective than at global scales; observation networks are too sparse to easily validate all the field scales present in a high‐resolution model simulation. In the AROME–France framework, OSEs experiments have been made concerning total zenith delays from ground‐based GPS stations (Yan et al , 2009; Boniface et al , 2009), radial winds from doppler radars (Montmerle and Faccani, 2009), radar reflectivities (Wattrelow et al , 2008), brightness temperatures from IASI (Infrared Atmospheric Sounding Interferometer; Guidard et al , 2011), water vapour mixing ratios from airborne lidars (Bielli et al , 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Due to its capabilities the WALES airborne demonstrator has become a state-of-the-art instrument for climate and meteorological research. Over the past decade it successfully completed several hundreds of flight hours in national and international field campaigns (Schäfler et al, 2010;Bhawar et al, 2011;Kiemle et al, 2011;Bielli et al, 2012;Fischer et al, 2013;Groß et al, 2014;Trickl et al, 2016).…”
Section: The Dlr Airborne Water Vapor Lidarmentioning
confidence: 99%